Hollow Alginate-Poly-L-Lysine-Alginate Microspheres Promoted an Epithelial-Mesenchymal Transition in Human Colon Adenocarcinoma Cells - Saberianpour, Shirin (Adv Pharm Bull, 2020)
Purpose: Today, there is an urgent need to develop a three-dimentional culture systems mimicking native in vivo condition in order to screen potency of drugs and possibly any genetic alterations in tumor cells. Due to the existence of limitations in animal models, the development of three dimensional systems is highly recommended. To this end, we encapsulated human colon adenocarcinoma cell line HT29 with alginate-poly-L-lysine (Alg-PLL) microspheres and the rate of epithelial-mesenchymal transition was monitored. Methods: Cells were randomly divided into three groups; control, alginate and Alg-PLL. To encapsulate cells, we mixed HT-29 cells (1 × 10(6) ) with 1 mL of 0.05% PLL and 1% Alg mixture and electrosprayed into CaCl2 solution by using a high-voltage power. Cells from all groups were maintained at 37˚C in a humidified atmosphere containing 5% CO(2) for 7 days. Cell viability was assessed by MTT assay. To monitor the stemness feature, we measured the transcription of genes such as Snail, Zeb, and Vimentin by using real-time PCR analysis. Results: Addition of PLL to Alg in a hallowed state increased the cell survival rate compared to the control and Alg groups (P<0.05). Cells inside Alg-PLL tended to form microcellular aggregates while in Alg microspheres an even distribution of HT-29 cells was found. Real-time PCR analysis showed the up-regulation of Snail, Zeb, and Vimentin in Alg-PLL microspheres compared to the other groups, showing the acquisition of stemness feature (P<0.05). Conclusion: This study showed that hallow Alg-PLL microspheres increased the epithelialmesenchymal transition rate after 7 days in in vitro condition. Such approaches could be touted as appropriate in vitro models for drug screening.